Learning Novel Word Meanings: An ERP Study on Lexical Consolidation in Monolingual, Inexperienced Foreign Language Learners. (15th June 2020) - Liu, Yushuang; van Hell, Janet G.
Abstract: Novel word learning and consolidation was studied in inexperienced language learners, to conceptually replicate and extend a similar study in experienced learners by Bakker, Takashima, Van Hell, Janzen, and McQueen (2015). Participants learned definitions for novel words on Day 1 and for another set of novel words on Day 2. Brain potentials collected in a semantic relatedness task revealed that learned words elicited a late positive component (LPC) priming effect after 24 hours but not on the day of learning. On Day 8, all previously learned words elicited LPC priming effects, but failed to modulate the N400. While LPC modulation emerged immediately after learning in the previous study of experienced learners, novel word meanings were found lexicalized only on Day 2 for inexperienced learners. Together, the findings suggest that novel word meaning lexicalization is gradual, and that prior language learning experience speeds up the process. Abstract :